PERAN SECOND HOME VISA DALAM PERWUJUDAN INDONESIA EMAS 2045 - Rezki, Muhadzib; Mulyawan, Budy; Febrianto, Arief (Journal of Administration and International Development, 2025)
The government is making diligent efforts to boost the Indonesian economy by attracting foreign investors to invest their capital in the country. One of the sectors that has been instrumental in driving economic growth is the immigration sector. In the context of supporting Golden Indonesia 2045, an important research endeavor has been undertaken to explore the challenges and opportunities in the field of immigration, as well as the crucial role of the second home visa in realizing this grand vision. In this research conducted using a qualitative normative juridical method, some fascinating results have been uncovered. The policy direction of the second home visa is clear: to stimulate the growth of the Indonesian tourism sector, which, in turn, will make a positive contribution to the national economy. The focus of this second home visa policy is aimed at foreign tourists with significant assets who wish to settle in Indonesia, enabling them to actively participate in supporting the country's economic growth. Consequently, Indonesia aims not only to become a golden nation by 2045 but also provides a golden opportunity for foreign investors who want to be part of this journey.